(untitled) (International Journal of Economics Management and Social Science, 2026)
This article examines the complex interplay between power relations, state legitimacy, and social movement dynamics in contemporary democratization processes. Drawing on recent developments documented in the Global State of Democracy 2025 report, which reveals that 2024 marked the ninth consecutive year of democratic decline globally, this study analyzes how political sociology frameworks illuminate persistent challenges to democratic governance. Through systematic analysis of theoretical perspectives on power, authority, and collective action, combined with empirical evidence from recent democratic transitions and authoritarian backsliding, this research demonstrates that understanding democratization requires attention to three interconnected dimensions: the distribution and exercise of power within political systems, the mechanisms through which states maintain or lose legitimacy, and the role of social movements in challenging or supporting existing power structures. The findings reveal that contemporary democratization faces a perfect storm of autocratic resurgence, declining press freedom (at 50-year lows), and acute uncertainty amid massive social and economic changes. However, cases from Bangladesh, Guatemala, and Senegal demonstrate that mass mobilizations can shift democratic trajectories when citizens unite to demand change. This article contributes to political sociology by integrating classical theories of power and legitimacy with contemporary empirical evidence, offering insights into both democratic erosion and resilience. Keywords: Political sociology, power relations, state legitimacy, social movements, democratization, democratic backsliding, collective action, political participation